2020 MEDAM Assessment Report on Asylum and Migration Policies in Europe. European and African perspectives on asylum and migration policy: Seeking common ground - Matthias Lücke; Olivia Sundberg Diez; Leonie Jegen; Franzisca Zanker (Kiel Institute for the World Economy (IfW), 2020)
The European Commission is currently finalizing its proposed New Pact on Migration and Asylum to re-start the debate on how to reform the common European asylum system and manage immigration from non-EU countries. One prominent concern is the 'external dimension': jointly managing migration to Europe with countries of origin and transit. By cooperating with countries of origin and transit across a wide range of policy areas, the EU and its member states may reduce irregular migration to Europe without undermining their humanitarian principles and impairing bilateral relations, which the present emphasis on securitizing the external EU border risks doing. In this 2020 MEDAM Assessment Report, we explore how European and African governments can reach common ground on jointly managing migration from Africa to Europe. – – Die Europäische Kommission finalisiert derzeit ihren Vorschlag für einen neuen Pakt zu Migration und Asyl, um die Debatte über die Reform des gemeinsamen europäischen Asylsystems und die Steuerung der Einwanderung aus Nicht-EU-Ländern wieder in Gang zu bringen. Ein wichtiges Anliegen ist dabei die "externe Dimension": die gemeinsame Steuerung der Migration nach Europa mit den Herkunfts- und Transitländern. Durch die Zusammenarbeit mit den Herkunfts- und Transitländern in einer Vielzahl von Politikbereichen können die EU und ihre Mitgliedstaaten die irreguläre Migration nach Europa verringern, ohne ihre humanitären Grundsätze zu untergraben und die bilateralen Beziehungen zu beeinträchtigen, was durch die gegenwärtige Betonung der Sicherung der EU-Außengrenze gefährdet wird. In diesem 2020 MEDAM Assessment Report untersuchen die MEDAM-Forscher, wie europäische und afrikanische Regierungen eine gemeinsame Grundlage für die gemeinsame Steuerung der Migration von Afrika nach Europa finden können.
Keywords: 320; Africa; asylum; international labor migration; EU policy; immigration policy; labour market policy; policy options